Optimalization of Marketing Strategy Innovation and Business Model Development: Study of The MAY a Water Refill Depot - Sanggarwati, Diah Ayu; Lestari, Sri; Suprihandari, Miya Dewi (JURNAL ILMIAH EDUNOMIKA, 2024)
Small and Medium Enterprises (SMEs) face a growing number of difficult business variables in the fast-paced globalization period, particularly in the face of intense competition and shifting consumer behavior brought on by technological improvements. The MAY refillable drinking water depot, situated in Surabaya, is one SME that has experienced a substantial decline in sales as a result of this rivalry. This article examines MAY Depot's marketing approach, which made use of the 7P marketing mix, SWOT analysis, and the creation of a Business Model Canvas (BMC) to identify creative solutions. This study employs a qualitative descriptive methodology to offer comprehensive insights into MAY Depot's market prospects and business issues. The end objective is to enhance the company's sustainability and competitiveness. It is anticipated that the research's conclusions will offer useful advice to companies in comparable circumstances. Keywords: Business Model Canvas, Marketing Strategy, SWOT Analysis.